Increased maternal and fetal cholesterol efflux capacity and placental cyp27a1 expression in pre-eclampsia - Mistry, Hiten D.; Kurlak, L.O.; Mansour, Yosef; Zurkinden, Line; Mohaupt, Markus; Escher, Genevieve (American Society for Biochemistry and Molecular Biology, 2017)
Preeclampsia is a pregnancy-specific condition that leads to increased cardiovascular risk in later life. A decrease in cholesterol efflux capacity is linked to CVD. We hypothesized that in preeclampsia there would be a disruption of maternal/fetal plasma to efflux cholesterol, as well as differences in the concentrations of both placental sterol 27-hydroxylase (CYP27A1) and apoA1 binding protein (AIBP). Total, HDL-, and ABCA1-mediated cholesterol effluxes were performed with maternal and fetal plasma from women with preeclampsia and normotensive controls (both n = 17). apoA1 and apoE were quantified by chemiluminescence, and 27-hydroxycholesterol (27-OHC) by GC-MS. Immunohistochemistry was used to determine placental expression/localization of CYP27A1, AIBP, apoA1, apoE, and SRB1. Maternal and fetal total and HDL-mediated cholesterol efflux capacities were increased in preeclampsia (by 10–20%), but ABCA1-mediated efflux was decreased (by 20–35%; P < 0.05). Maternal and fetal apoE concentrations were higher in preeclampsia. Fetal plasma 27-OHC levels were decreased in preeclamptic samples (P < 0.05). Placental protein expression of both CYP27A1 and AIBP were localized around fetal vessels and significantly increased in preeclampsia (P = 0.04). Placental 27-OHC concentrations were also raised in preeclampsia (P < 0.05). Increased HDL-mediated cholesterol efflux capacity and placental CYP27A1/27-OHC could be a rescue mechanism in preeclampsia, to remove cholesterol from cells to limit lipid peroxidation and increase placental angiogenesis.